Large intra-individual variability of plasma cytokines in healthy young men: a two 24-h study over a month. Issue 2 (3rd March 2016) - Selmaoui, Brahim; Sackett-Lundeen, Linda; Haus, Erhard; Touitou, Yvan
Abstract : Cytokine levels in blood are not yet fully considered as biomarkers for disease even if some significant progresses have been made in linking certain cytokines to some diseases. The aim of this study was to look for the stability of some cytokines in blood collected in two different days separated by one month. Fifteen healthy young men aged 20–30 years were selected for this study. Each subject participated in two 24-h sessions spaced a month apart. Blood sample was taken at 11:00, 17:00, 22:00, 01:00, 04:00, 06:00, and 08:00. Concentrations of interleukin-6, interleukin-1-receptor antagonist, soluble IL-2 receptor, interleukin-1 beta, and interleukin-2 were measured in serum. The circadian pattern of each variable was compared between the two days. The results show that there is no reliability for the measured cytokines. This study shows that cytokine levels measured in blood are neither reliable variables nor considered as stable markers in healthy subjects.